Epidural abscess formation after chemotherapy for breast cancer: a case report and literature review - An, Youzhi; Li, Lili; Liu, Qingning; Zhang, Zhen; Lin, Xuelin (Frontiers in Surgery, 2025)
IntroductionSpinal epidural abscess is a rare infectious lesion of the central nervous system. Here, we report a rare case of a thoracic suppurative epidural abscess in a female patient who developed incomplete paralysis of both lower limbs after chemotherapy for breast cancer. She underwent surgery and recovered well after surgery.Case reportA 49-year-old female patient developed an epidural abscess after chemotherapy for breast cancer; she suffered sudden pain and paralysis in both lower limbs. Thoracic T9–T11 laminectomy, abscess removal, bone grafting, fusion, and internal fixation were performed. After the operation, the muscle strength in both lower limbs gradually recovered.DiscussionThis is the first reported case of an epidural abscess after chemotherapy for breast cancer. The disease progresses rapidly. During the literature review process, we found that timely removal of the epidural abscess, combined with the administration of appropriate antibiotics at the same time, is crucial for improved healing and successful treatment.